Prevalence of hypertension among adult type-2 diabetes patients: a preliminary study in Kuantan, Pahang, Malaysia - Abdullah, Fa’iza; Tin, Myo Han; Mat Nor, Mohd Basri; Md Aris, Mohd Aznan; Ismail, Ida Zuriaty (International Islamic University Malaysia, 2015)
Hypertension (HPT)is most common co-morbidity among type-2 diabetes mellitus (T2DM) patients which ominously increased their morbidity and mortality from cardiovascular disease (CVD)